Current nutritional status assessment tools for metabolic care and clinical nutrition. Issue 5 (September 2019) - Taberna, Daniel J.; Navas-Carretero, Santiago; Martinez, Jose A.
Abstract : Purpose of review: The aim of this report is to critically review existing questionnaires and tools to assess nutritional status in different populations and pathological conditions. Recent findings: A total of 16 instruments to evaluate nutritional status were recorded, which were based on anthropometrical determinations, biochemical markers, clinical examinations and subjective questionnaires, depending on the nutritional assessment focus, involving different concepts: screening of the risk, diagnosis and severity of malnutrition, as well as the consequences of undernutrition or overnutrition. Summary: A variety of questionnaires, equations and tools were found with ability to assess nutritional status for metabolic care or clinical nutrition purposes, but apparently there is no optimal, universal and reliable nutritional status screening system for all metabolic conditions. Novel assessment instruments should provide high sensibility and specificity, be precise and reliable as well as inexpensive and simple, in order to avoid the additional burden of excessive loads of costs, work and time while dynamically overcoming the influence of disease diversity.